A valorização do antigo pelo novo: o panorama da inserção de arquitetura contemporânea nos conjuntos históricos tombados de Mariana e Ouro Preto - Tatiana da Silva Gomes (2009)
The insertion of contemporary architecture in historical and preserved groups in Brazil is still a little explored theme that presents a list of isolated interventions, where more pastiches and reconstructions occur. With the intention of going deeper in the discussion, the Study of the new architecture insertion in Mariana and Ouro Pretos preserved and historical groups was proposed. The choice of these two cities is due to the fact that they have been the stage of the first actions of IPHAN, and because they have had copies of all architectural currents since theoccupation of mineiro territory. As a starting point, it will be proposed a revision of the main documents produced in meetings relating to the cultural patrimony preservation, illustrated with the most daring international experiences. Then seek to understand how the translation of these concepts occurred for the Brazilian context, through the study of the architectural typologies evolution and the analysis of the main Brazilian cities revitalization projects. Finally, approach the study subject with the construction of a report of Mariana and Ouro Pretos architecturalaspects, highlighting the new architectures insertion issue; and in comparative character, present the case studies that are: the Residence of Marianas Archbishop, and the Cultural and Tourist Center of FIEMG system, looking forward in knowledge of an always controversial issue, and indentify possible solutions.